HUBUNGAN TINGKAT PENDIDIKAN DAN PEKERJAAN IBU DENGAN PERILAKU PENCEGAHAN ISPA PADA BALITA DI WILAYAH KERJA PUSKESMAS GANG SEHAT PONTIANAK - ., Annisa Firdausia (Jurnal Mahasiswa PSPD FK Universitas Tanjungpura, 2013)
BackgroundAcute Respiratory Infection (ARI) is an acute infection ofrespiratory tract from the nose to alveol including the adnexa of lung. Thehighest prevalence is in children under 5 years old. Family plays importantrole at ARI's prevention, especially mother, association of mother's educationand employment to prevention of ARI will be studied.ObjectiveThe aims to see the association between mother's education andemployment to prevention of acute respiratory infection in children under 5years old.MethodAnalitical cross sectional study. Data were gained from thequestionnaire filled by mothers who fit sampling criteria in Posyandu ofPuskesmas Gang Sehat on February to March 2012.ResultThere are 28 repondents taken as sample. Most of the samples havegood prevention of ARI (46,4%), 42,9% of the samples are fair, and 10,7%have less level prevention of ARI. Data was analyzed by KolmogorovSmirnovtest,resultingmother'seducationwasassociatewithpreventionofARIinchildrenunder5yearsold(p=0,001),andalsomother'semploymentwasassociatewithpreventionofARIinchildrenunder5yearsold(p=0,013).Thehighereducationresultingbetterprevention,sodotheunemploymother.ConclusionMotherwithhighereducationtendtohavebetterpreventionofARI,sowithunemploymotheraswell.HealtheducationisneededbymothertoincreaseknowledgeaboutpreventionofARIinchildrenunder5yearsold.Keywords: acute respiratory infection (ARI), education, employment,prevention